Concurrent presence of secretory carcinoma and Warthin's tumor in ipsilateral parotid gland. (October 2020) - Kaleem, Arshad; Patel, Neel; Alzahrani, Shadi; Hatoum, Hisham; Tursun, Ramzey
Highlights: Synchronous tumors in salivary glands should be considered during workup. Consider malignancy in lesions with aggressive features like pain and rapid growth. Intraoperative frozen sections are a useful adjunct in salivary gland masses. Abstract: Background: The presence of synchronous benign and malignant salivary gland neoplasms is very rare. The authors present a previously unreported combination of Secretory Carcinoma (SC) and Warthin's Tumor (WT) within the same parotid gland. Methods: The patient presented with increasingly painful enlargement of the left parotid gland. CT scan with contrast revealed a heterogeneous solid/cystic mass in the superficial lobe. Fine needle aspiration cytology favored pleomorphic adenoma (PA) and patient underwent superficial parotidectomy without complication. Results: Final pathology revealed concomitant presence of SC and WT. Stains were positive for S100 and mammaglobin, and FISH revealed the presence of t(12;15) (p13;q25) translocation, resulting in the ETV6-NTRK3 fusion gene. Conclusion: It is important for surgeons and pathologists to note the potential for co-existing benign and malignant pathology within the same salivary gland, as this can have an impact on management and prognosis for patients.